2020
DOI: 10.3390/antibiotics9050221
|View full text |Cite
|
Sign up to set email alerts
|

Screening and Molecular Docking of Novel Benzothiazole Derivatives as Potential Antimicrobial Agents

Abstract: The burden of antibiotic resistance necessitates a continued search for new antimicrobials. We evaluated the antimicrobial activities of novel benzothiazoles synthesized by our group. Antibacterial activity was evaluated in vitro in Staphylococcus aureus, Bacillus subtilis, and Escherichia coli, while the antifungal activity was tested in Candida albicans and Aspergillus niger, and expressed as the minimum inhibitory concentration (MIC; µg/mL). MIC values of benzothiazole compounds ranged from 25 to 200 µg/mL.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
44
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 53 publications
(82 reference statements)
0
44
0
Order By: Relevance
“…We have replaced 6-trifluoromethoxy substituent of benzothiazole ring first by 6-CN, 6-Ad, 4-Me-6-Ad and after by 4-OCH3, and 6-Cl keeping the same substitution at position 4 of benzene ring mostly for 6-Cl, 4-OMe and in some cases of 6-CN (Figure 2). Thus, we synthesized 2-(2-(substituted phenyl)-4-oxothiazolidin-3yl)benzo [d] (15)(16)(17)(18)(19).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have replaced 6-trifluoromethoxy substituent of benzothiazole ring first by 6-CN, 6-Ad, 4-Me-6-Ad and after by 4-OCH3, and 6-Cl keeping the same substitution at position 4 of benzene ring mostly for 6-Cl, 4-OMe and in some cases of 6-CN (Figure 2). Thus, we synthesized 2-(2-(substituted phenyl)-4-oxothiazolidin-3yl)benzo [d] (15)(16)(17)(18)(19).…”
Section: Resultsmentioning
confidence: 99%
“…It is worth mentioning that benzothiazole is a privileged heterocyclic scaffold with multiple applications and tremendous range of pharmacological activity. Benzothiazoles are recognized for their anti-inflammatory [ 12 , 13 , 14 ], antimicrobial [ 15 , 16 , 17 , 18 , 19 ], anesthetic [ 20 ], anticancer [ 21 , 22 , 23 ], anti-viral [ 24 , 25 , 26 ], analgesic [ 13 , 14 ], antipyretic [ 27 ], antidiabetic [ 28 , 29 , 30 ], antioxidant [ 12 , 16 , 20 , 21 , 31 ], carbonic anhydrize inhibitory [ 26 , 32 , 33 ], anticonvulsive [ 34 , 35 ], antifungal [ 33 , 36 , 37 ] and many other [ 38 , 39 ] activities. Additionally, the benzothiazole scaffold is present in three FDA approved drugs ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Benzothiazole derivatives have fascinating interest due to their varied biological activities viz. antioxidant, anti‐inflammatory, [2] neuroprotective, [3] anti‐proliferative, [4] anti‐diabetic, [5] antimicrobial, [6] antitumor, [7] analgesic, [8] anti‐gastric cancer, [9] anticonvulsant, [10] antinociceptive, [11] anti‐tubercular, [12] anthelmintic, [13] antiviral, [14] histamine H 3 antagonist, [15] appetite depressants, [16] and muscle relaxant [17] activities. In addition, the anticancer action of benzothiazole compounds has been extensively applied in recent years [18] .…”
Section: Introductionmentioning
confidence: 99%
“…Two papers in this special issue present two approaches to optimize the antimicrobial activity of compounds previously described as having antimicrobial activity. The paper by Morsy et al describes the experimental screening of antimicrobial activities of benzothiazole derivatives against selected bacteria and fungi [4]. The studies were complemented by computer-assisted molecular docking studies, as benzothiazoles were previously demonstrated to inhibit Escherichia coli dihydroorotase [4].…”
mentioning
confidence: 99%
“…The paper by Morsy et al describes the experimental screening of antimicrobial activities of benzothiazole derivatives against selected bacteria and fungi [4]. The studies were complemented by computer-assisted molecular docking studies, as benzothiazoles were previously demonstrated to inhibit Escherichia coli dihydroorotase [4]. In order to gain new insights into the structure/antimicrobial activity relationships, Alves et al synthesized cyclam derivatives, mono-and trans-disubstituted with benzyl, methylbenzyl, trifluoromethylbenzyl, or trifluoroethylbenzyl moieties appended to the macrocyclic ring nitrogen atoms [5].…”
mentioning
confidence: 99%